Prescribing pattern of non-steroidal Antiinflammatory drugs at outpatient departments of government hospital and private clinic in Sabah state - Md. Shamsur Rahman (Universiti Malaysia Sabah, 2012)
The main objective of this study was to obtain baseline information regarding the prescribing pattern of non-steroidal anti-inflammatory drugs (NSAIDs) by the qualified medical personnel in the outpatient departments (OPOs) of two selected clinics in Kota Kinabalu, Sabah, Malaysia. A total of 400 prescriptions containing NSAIOs (200 from each outpatient department of each clinic) were collected, photocopied and later analyzed. The clinical conditions for which NSAIOs prescribed were identical in two clinics, although there were wide variations in the prescribing pattern with respect to pharmacological sub-classes of NSAIDs. Analgesics with no or minimal anti-inflammatory effects became the most commonly prescribed NSAIDs in the outpatient department of UMS polyclinic (UPC). On the contrary, analgesics with potent anti-inflammatory effects became the most commonly prescribed NSAIDs in the outpatient department of private polyclinic (PPC). Moreover, the prescribers in PPC had to prescribe additional drugs than those of the prescribers of UPC. Ultimately, the cost of prescribed NSAIDs per prescription and the cost of total drugs per prescription became greater in PPC compared to UPC. It may be mentioned that overall prescribing pattern of NSAIDs among two clinics is satisfactory, although there may be scopes for improvement by introducing appropriate educational intervention for rational prescribing.